Comparison of Tp-e interval, QTc interval and Tp-e/QTc ratios between non-diabetic and prediabetic population - Ardahanli, Isa; Celik, Mehmet (Annals of Medical Research, 2021)
Aim: Increased blood glucose concentration and cardiac autonomic nerve dysfunction are associated with an increased risk of malignant ventricular arrhythmia. Tp-e interval, Tp-e/QT, and Tp-e/QTc are novel parameters used to assess ventricular arrhythmogenicity. This study aimed to compare these parameters with the healthy control group in prediabetics. Materials and Methods: The ECGs of 58 prediabetic patients (29 male, 59.74 ±13.25 years) were examined and matched with the ECGs of 59 healthy controls (28 male, 61.75 ± 12.66 years) that were matched with gender, age and body mass index. From the 12-lead ECG Tp-e and QT intervals were measured and by Bazett's formula QTc was calculated. Tp-e/QT and Tp-e/QTc proportions were also determined. Results: In prediabetic patients, the mean Tp-e interval was significantly longer than the control group (79.07 ± 8.17 vs 72.03 ± 9.77 ms, respectively; p 0.001). Also in prediabetic, Tp-e/QT and Tp-e/QTc were significantly higher than the controls (respectively 0.21 ± 0.25 vs 0.19 ± 0.03 and 0.19 ± 0.02 vs 0.17 ± 0.02; p 0.001). Other ECG parameters were similar in both groups. HbA1c levels and glucose levels were positively correlated with Tp-e / QT and Tp-e / QTc.Conclusion: Prediabetes increases the risk of ventricular arrhythmogenesis by increasing the transmural dispersion of repolarization. The addition of Tp-e interval and TP-e / QT measurements to the routine ECG evaluation of prediabetic patients can be used to predict arrhythmia risk.
Keywords: Prediabetes; Tp-e interval; Tp-e/QT ratio; Tp-e/QTc ratio; ventricular arrhythmia